The pastoral home school: rural, vernacular and grassroots literacies in early Soviet Mongolia - Marzluf, Phillip P. (My University, 2014)
Literacy before and after the 1921 People's Revolution in Mongolia has been largely represented by socialist historiography and post-socialist urban perspectives, which have rendered unofficial and non-pragmatic literacies invisible. This study explores rural, vernacular and grassroots literacy theories to recontextualize the pre-revolutionary category of Mongolian home schooling and to offer a new perspective – pastoral literacy – which enables historians and other researchers of Central Asia to represent the literacy practices of non-urban semi-nomads more accurately and vividly. This study applies the pastoral literacy perspective to literacy narratives extracted from University of Cambridge Oral History of Twentieth Century Mongolia interviews and demonstrates that pastoral home schooling was a socially and culturally salient domain for acculturating young Mongolians into the 1960s. Mongolian pastoral home schooling consisted largely of personal, male teacher–student relationships, authoritative teaching models, alphabet-based curricula, as well as texts and materials adapted from dominant religious and state literacies.
Citation: Phillip P. Marzluf (2014) The pastoral home school: rural, vernacular and grassroots literacies in early Soviet Mongolia, Central Asian Survey, 34:2, 204-218, DOI: 10.1080/02634937.2014.991611
Keywords: Mongolia; Literacy; Home Schooling; Rural; Socialism